Safety and health improvement in a process industry [compact disc] - 279800 Theveram, Pancharam (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Industri)) - Universiti Teknologi Malaysia, 2005